Multicultural Education in the Forming of Social Character in the Digitalization Era - Surahman, Susilo; Pratiwi, Ratih; Imron, Ali; Cakranegara, Pandu Adi; Putra, Purniadi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The purpose of the study was to find out the implementation of multicultural education studies in the digital era and the implications of multicultural education on the formation of social character in the digitalization era, with the rapid development of technology today, it certainly has an impact on the condition of education, including the study of multicultural education. The method used in this article is a qualitative method with a literature review. Data collection techniques are carried out with a conceptual approach. The data collection technique in this study was carried out with documentation techniques. This technique is used to track documents, data, and information in books, magazines, scientific journals, articles, and so on that are relevant to this research. The author uses content analysis (content analysis) to analyze the data. The results of the study show that the condition of the rapid progress of information and communication technology has a negative impact. Therefore multicultural education, in this case, seeks to provide understanding to the community, especially students, to know about multicultural values, namely the attitude of accepting, appreciating, and respecting all forms of difference. To avoid unwanted conditions such as radicalism, racism, discrimination, and so on.